The Effect of Providing Educational Videos on the Level of Knowledge and Attitudes of Adolescent Girls About Dysmenorrhea at SMA Negeri 1 Palangka Raya - Sukriani, Wahidah; Salim, Stevany Paskarina; Bingan, Eline Charla Sabatina (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2024)
World Health Organization states that dysmenorrhea affects 1,769,425 women (90%), with 10-15% experiencing severe dysmenorrhea. The incidence rate of dysmenorrhea among productive-aged women in Indonesia ranges from 45%-95%. A preliminary study at SMA Negeri 1 Palangka Raya revealed that 86.7% of the students experienced dysmenorrhea, while 13.3% did not. Students who experience dysmenorrhea have different ways of managing it. Therefore, accurate information on managing dysmenorrhea is needed for the students at SMA Negeri 1 Palangka Raya. If not addressed, dysmenorrhea can cause mental and physical tension in teenagers, affecting their daily activities. Objective: To analyze the effect of providing educational videos on the knowledge and attitudes of female teenagers about dysmenorrhea at SMA Negeri 1 Palangka Raya.. Methodology: This research employs a pre-experimental design with a one-group pre-test post-test group design. The sample consists of 80 female teenagers from SMA Negeri 1 Palangka Raya. Results: The results indicate an increase in knowledge and attitude levels after providing educational videos to the female teenagers at SMA Negeri 1 Palangka Raya (p-value < 0.05). Conclusion: It is expected that these educational videos can be used to improve the knowledge and attitudes of female teenagers in dealing with dysmenorrhea.